Comparative study of spin-dependent transport in Co2FeAl/MgAl2O4/CoFe magnetic tunnel junctions with and without thin CoFe interface insertion: an elastic and inelastic scattering model analysis. (12th November 2019) - Scheike, Thomas; Sukegawa, Hiroaki; Ohkubo, Tadakatsu; Hono, Kazuhiro; Mitani, Seiji
Abstract: We compare structural and transport properties of Co2 FeAl (CFA)/MgAl2 O4 (MAO)/CoFe magnetic tunnel junctions (MTJs) with and without a 1 nm thick CoFe insertion layer. While the two MTJs show a large difference in resistance area ( RA ) product, there is no significant difference in their stacked structures such as the thickness of an MAO barrier. Temperature ( T ) dependence of tunneling conductance ( G P and G AP for parallel and antiparallel configurations, respectively) was investigated for the two MTJs, as well as their tunnel magnetoresistance that exceeds 200%. The most striking feature of the temperature dependence is that non-monotonic change appeared by inserting the CoFe layer, i.e. negative d G P /d T emerged only in the CFA/1 nm CoFe/MAO/CoFe MTJ. The observed results of G P and G AP were analyzed in a model proposed by Hu et al (2016 Phys. Rev . B 94, 094428), in which elastic (spin-conserved) and inelastic (spin-flip scattering) terms were considered. We found that the non-monotonic change observed in T dependence of G P is associated with dominance of the elastic tunneling term. This study demonstrated that the model analysis of T dependence of G P can give insight into the microscopic transport mechanism.